Can experience modulate handler responses to boxes designed to decrease musculoskeletal load?*. Issue 6 (3rd June 2017) - Nogueira, Helen Cristina; Silva, Luciana Cristina da Cunha Bueno; Coury, Helenice Jane Cote Gil; Barbieri, Dechristian França; Oliveira, Ana Beatriz
Abstract: Biomechanical load during the handling of commercial (cardboard box with and without cut out) and non-commercial boxes (cardboard box with a retreat on the bottom edges), on experienced compared to inexperienced subjects was evaluated. Thirty-seven inexperienced and 21 experienced workers handled all boxes at shoulder and ground levels. Biomechanical load on upper limb was investigated through posture and electromyography (EMG) recordings. Comfort and effort were assessed immediately after each handling. In general, experienced workers had low range of motion. On the other hand, EMG was similar between both groups, except when non-commercial boxes were handled in non-favourable heights. Comfort was higher when a non-commercial box was handled versus a commercial one, regardless of the group. Both groups had a lower biomechanical load when handling the non-commercial boxes compared to the commercial ones. However, experienced workers did not have the same advantage as inexperienced subjects when handling those new boxes. Practitioner Summary : Box designs favouring intuitive hand coupling and more efficient postures have potential to reduce the risk of upper-limb musculoskeletal disorders in inexperienced subjects. However, ergonomist has to deal with workers on different levels of experience. Results of this study can support the development of effective recommendations for the working context.